Adversidade do nutricionista para o processo de aquisição de gênero da agricultura familiar de determinadas regiões intermediárias do Estado do Pará - CRESCÊNCIO, Josiane Pantoja (2023)
Objective: To analyze the main adversities of nutritionists who are technically responsible (TR) for the gender acquisition process of family farming (FF) in certain intermediate regions of the state of Pará. Method: Cross-sectional study with a quali-quantitative approach, carried out in some intermediate regions of the state of Pará, from 2019 to 2021, carried out by CECANE/UFPA. We selected 20 municipalities that had a percentage of less than 30% of purchases from FF. The study started by contacting the TR, in each region, via phone call and social media and by email, where the link to access the Google Forms® tool, version n. 0.8/2015, was sent to fill in the questionnaire with multiple-choice open and closed questions about the National School Feeding Program -NSFP. Data were tabulated in Microsoft Excel® software and analyzed in accordance with NSFP legislation. Results: It was observed that most of the nutritionists had the link through temporary contracts, lack of technical staff, difficulties in participating in public calls and in the elaboration of the term of reference. In relation to farmers and municipal management, it is worth noting the non-receipt of sales project proposals, to contemplate the purchase guidelines in the public notice, insufficient quantity of local production, lack of product varieties, unfeasibility of producers, regarding the supply regularization of foodstuffs and non-compliance with contracts through farmers, items for which they affect the acquisition of FF products. In the pandemic (2020), the following were identified: lack of structure and storage for FF products and their inclusion in the composition of food kits. Conclusion: The main adversities of the TR found in this study (lack of technical staff, impasse with the public call and obstacles related to farmers and the executing entity) emphasize the importance of the nutritionist in the process of acquiring foodstuffs from the FF, since the same it is an essential element for the proper execution of the NSFP.